Seasonal dynamics and management of whitefly ( Bemesia tabaci Genn.) in tomato ( Solanum esculentum Mill.) - Sharma,Devinder (2017)
ABSTRACT Studies on seasonal dynamics of white fly (Bemesia tabaci) on tomato (Solanum esculentum var. Pusa Ruby) revealed that it appeared first during the 13th and reached maximum during 21st standard meteorological week. A positive correlation between adult population and abiotic factors viz. temperature (maximum and minimum) and sunshine hours was observed, whereas humidity (maximum and minimum) and rainfall showed a negative correlation with it. Taken together, the key weather parameters studied, caused 89.00 per cent variation in whitefly population (R2 value). Combination of carbofuran (soil application) + imidacloprid (seed treatment ) + imidacloprid (foliar application) proved significantly superior and caused maximum reduction in whitefly population followed by imidacloprid (seed treatment) + thiomethoxam (spray), imidacloprid (seed treatment) + imidacloprid (spray), imidacloprid (seed treatment) + dimetheoate (spray), carbofuran (soil application) + malathion (spray), and imidacloprid (seed treatment) + yellow sticky traps. The highest cost benefit ratio of 1:25.04 was recorded in case of carbofuran (soil application) + imidacloprid (seed treatment ) + imidacloprid (foliar application) followed by 1:22.38 for imidacloprid (seed treatment) + thiomethoxam (spray) ; 1:21.81 for imidacloprid (seed treatment) + imidacloprid (spray); 1:19.27 imidacloprid (seed treatment) + dimetheoate (spray); 1:19.48 carbofuran (soil application) + malathion (spray), and 1:8.33 for imidacloprid (seed treatment) + yellow sticky traps. The soil application of carbofuran + seed treatment with imidacloprid and three foliar sprays of imidacloprid at fortnight interval starting 40 days after transplanting is found effective and is advised for whitefly management in susceptible tomato cultivars.